2019
DOI: 10.1002/jor.24194
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance of cementless total knee replacements: It is not all about the maximum loads

Abstract: Finite element (FE) models are frequently used to assess mechanical interactions between orthopedic implants and surrounding bone. However, FE studies are often limited by the small number of bones that are modeled; the use of normal bones that do not reflect the altered bone density distributions that result from osteoarthritis (OA); and the application of simplified load cases usually based on peak forces and without consideration of tibiofemoral kinematics. To overcome these limitations, we undertook an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…Interestingly, the increase in micromotion (79% for total and 37% for shear) was larger than the 22% increase in the varus‐valgus joint moment (from 27.7 to 33.7 Nm). Our findings are consistent with prior studies that found that the worst‐case scenario for the bone‐implant interaction involves submaximal loads 20–22,32 . Moreover, our values of shear micromotion are within the range 26 to 63 µm found experimentally by Chong et al 20 …”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the increase in micromotion (79% for total and 37% for shear) was larger than the 22% increase in the varus‐valgus joint moment (from 27.7 to 33.7 Nm). Our findings are consistent with prior studies that found that the worst‐case scenario for the bone‐implant interaction involves submaximal loads 20–22,32 . Moreover, our values of shear micromotion are within the range 26 to 63 µm found experimentally by Chong et al 20 …”
Section: Discussionsupporting
confidence: 93%
“…However, aseptic loosening continues to be the leading cause of revision for TKA, accounting for 31%-39% of revision cases [ 1 , 2 ]. Cement fixation provides robust initial fixation; however, it is subject to tensile and shear forces, which are not well tolerated and can lead to micromotion and component loosening [ 25 , 26 ]. Cementless fixation provides the opportunity for biologic ingrowth with the potential for long-term remodeling and eliminates the risk of cement particle third-body debris [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cement fixation provides robust initial fixation; however, it is subject to tensile and shear forces, which are not well tolerated and can lead to micromotion and component loosening [ 25 , 26 ]. Cementless fixation provides the opportunity for biologic ingrowth with the potential for long-term remodeling and eliminates the risk of cement particle third-body debris [ 25 , 26 ]. This biologic fixation may lower the incidence of aseptic loosening and could provide a superior option for patients most at risk of loosening, namely young and obese patients [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These load conditions are not representative of the complex and dynamic loading environment at the ankle during daily activities, which includes multiaxial forces and moments. In other implant systems, such as the tibial component of total knee arthroplasty, the most critical scenario for the interaction between the implant and the bone has been shown to be the result of complex combinations of submaximal loads and relatively high multiaxial moments 9–12 . Thus, even though McInnes et al 7 and Sopher et al 8 showed that different fixation designs respond differently to applied loads, it remains unclear how these same fixation designs would behave under the complex loading scenarios.…”
Section: Introductionmentioning
confidence: 99%